A companion to world mythology - Barber, Richard W.; Baynes, Pauline (New York : Delacorte Press, 1979)
Alphabetically lists the gods of such diverse cultures as Polynesia, Japan, and ancient Greece, with substantial accounts of their exploits.
Includes indexes.
Keywords: Mythology -- Juvenile literature; Mythology